Analysis of the complete organellar genomes of the Streaked Rosefinch Carpodacus rubicilloides on the Tibet Plateau. Issue 1 (2nd January 2019) - Qin, Jinlan; Li, Guopan; Li, Wei; Jin, Zhenyu; Li, Shaobin
Abstract: The Streaked Rosefinch ( Carpodacus rubicilloides ) is a poorly-known bird species distributed in China and Himalayas. In this paper, we described the whole mitochondrial genome of the Streaked Rosefinch. The entire mitochondrial sequences were determined using long-range PCR and conserved primer walking approaches. The results demonstrated that the whole mitochondrial genome of C. rubicilloides was 16, 805 bp in length with 53.9% A + T content; the genome harbored the same gene order as that of other passerine birds, including 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and 1 non-coding control region. The control region (D-loop) of C. rubicilloides was located between tRNA-Gln and tRNA-Phe with 1228 bp length. Phylogenetic analysis indicated that the genome of Carpodacus species clustered within a clade and is closer related to other Fringillidae species than Anatidae species. These mitochondrial data are potentially important for the further studies on molecular evolution and conservation genetics in true finch species.